Von Willebrand factor multimer structure is neither acutely nor chronically affected by plateletpheresis - Weiss, Dominik R; Dankerl, Helen; Martin, Alexander; Strasser, Erwin F; Ringwald, Jürgen; Eckstein, Reinhold; Zimmermann, Robert (Clinical Laboratory, 2014)
Plateletpheresis (PltPh) exposes the donor's blood to artificial surfaces and mechanical forces such as shear stress and centrifugation. In terms of the donor's safety and the quality of the apheresis platelet concentrate (APC), possible impairment of platelet function due to PltPh should be excluded. Von Willebrand factor (VWF) plays a pivotal role in platelet adhesion and aggregation. VWF is a multimeric protein and can be damaged by adsorption or shear stresses. It is unclear whether VWF structure could be damaged during PltPh, leading to platelet dysfunction.We analyzed VWF antigen (VWF:Ag), ristocetin cofactor (VWF:RCo), and VWF multimer structure immediately before and after apheresis in the donor and in the APC. These parameters and factor VIII activity (FVIII:C) and closure time using PFA-100 (CT) were also analyzed in blood samples taken from new donors before the first and before subsequent donations and from long-term donors.During apheresis, VWF:Ag falls by about 15% but the VWF multimer structure remains unchanged. In samples taken before subsequent donations, there was a tendency of VWF:Ag and FVIII:C to increase throughout the initial donations, but no alteration of multimer structure. Long-term donors, however, show a normal VWF multimer structure and normal concentrations of VWF:Ag, VWF:RCo, and FVIII:C. In some donors with low-normal VWF:Ag and VWF:RCo, PFA-100 CT was prolonged.VWF multimer structure is neither acutely nor chronically affected by plateletpheresis. A decrease in VWF:Ag with no functional damage only occurs acutely and can be explained by the withdrawal of plasma and dilution with the anticoagulant ACD-A due to apheresis.
EVALuna2:15985